Designing swiftlet farming using energy plus - Frezzal, Faisal. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The swiftlet farming is a new type of business that is gradually growing in our country. Swiftlet farming can be defined as the conversions of people - centric buildings into buildings used to house and protect a certain species of swiftlets . Swiftlets are being lured into these buildings with the purpose of collecting their valuable bird nest. This method is more efficient comp ared to the traditional method of bird - nest harvest and can ensure the preservation of the swiftlet population. Constant attention and involvement from a lot of people and different organizations cause the swiftlet farming to undergo a lot of development a nd research to expand the industry. Different types of material and designs of swiftlet farms are being created to cater the needs of the swiftlets. The different aspects of building construction such as the orientation of the building, the wall materials and designs and also the roof aspects have a significant effect to the suitable environment for the swiftlets. With the various available materials and designs exist, the most preferable options are being chosen to minimize the investment and to avoid furt her problems occur.